(untitled) (Research, Society and Development, 2021)
Strongyloides stercoralis is a helminth with worldwide distribution and has the capacity to promote intestinal infection, which may progress to disseminated strongyloidiasis. The clinical manifestations of disseminated strongyloidiasis vary widely and immunocompromised patients are at risk of symptomatic infection. A 38-year-old man was submitted to double kidney-pancreas transplantation in December 2019 due to type 1 diabetes mellitus and chronic dialysis renal failure. He was admitted to the kidney transplant infirmary with nausea, vomiting and abdominal pain, which had started 5 days before. With the diagnostic possibility of infectious gastroenteritis, antibiotic therapy was started. The patient evolved with worsening ventilation associated with a decline in sensorium, being referred to the Intensive Care Unit, where he was intubated and placed on ventilatory support. As the patient was critically-ill and hemodynamically unstable, he required vasoactive drugs and antibiotic therapy. A purple serpiginous lesion was observed in the abdomen, and then the possibility of disseminated strongyloidiasis was raised, which was later confirmed by positive gastric wash and tracheal aspirate cultures . Subcutaneous ivermectin was started, due to the impossibility of intestinal absorption and due to hemodynamic instability and high gastric residue. Four days after the start of ivermectin and culture-guided antibiotic therapy, the patient died. Disseminated strongyloidiasis continues to be considered a global health challenge, particularly in the transplanted population, in which the infection is correlated with a high mortality. The diagnosis is often delayed and should be considered in the differential diagnosis of patients with multiple-organ failure.